2021
DOI: 10.3390/pharmaceutics13111766
|View full text |Cite
|
Sign up to set email alerts
|

Surface Treatment of Glass Vials for Lyophilization: Implications for Vacuum-Induced Surface Freezing

Abstract: Freeze-drying is commonly used to increase the shelf-life of pharmaceuticals and biopharmaceuticals. Freezing represents a crucial phase in the freeze-drying process, as it determines both cycle efficiency and product quality. For this reason, different strategies have been developed to allow for a better control of freezing, among them, the so-called vacuum-induced surface freezing (VISF), which makes it possible to trigger nucleation at the same time in all the vials being processed. We studied the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
1
8
1
Order By: Relevance
“…The RMC of the NDV-VFD vaccine was detected using thermogravimetric analysis (Merivaara et al 2021 ; Osman et al 2021 ; Regis et al 2021 ). To determine the RMC after drying, eight vials of each vaccine preparation were weighed before and after drying at 80℃ for 2 h without a stopper.…”
Section: Methodsmentioning
confidence: 99%
“…The RMC of the NDV-VFD vaccine was detected using thermogravimetric analysis (Merivaara et al 2021 ; Osman et al 2021 ; Regis et al 2021 ). To determine the RMC after drying, eight vials of each vaccine preparation were weighed before and after drying at 80℃ for 2 h without a stopper.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrophobic coatings promoted boiling and blow-up phenomena while hydrophilic coatings increased the risk of fogging. In the case of hydrophobic coatings, the addition of surfactant and degasification step prior to nucleation allowed to significantly reduce bubbling for a successful induction of nucleation (Regis et al 2021).…”
Section: Key Elementsmentioning
confidence: 99%
“…The findings of the MD simulation study revealed that the hydrophobic coating could stimulate the formation of bubbles and cause a faster liquid film break-up, resulting in a decrease in the onset temperature of explosive boiling [20]. A study conducted by Regis et al (2021) to investigate the effect of hydrophilic and hydrophobic surfaces on vacuum-induced surface freezing (VISF) showed that the hydrophobic surface promotes boiling and blow-up phenomena that could result in the formation of unacceptable defects on the glass surface. Although, the hydrophilic surfaces caused an increased risk of fogging on the inner vial surface [21].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Regis et al (2021) to investigate the effect of hydrophilic and hydrophobic surfaces on vacuum-induced surface freezing (VISF) showed that the hydrophobic surface promotes boiling and blow-up phenomena that could result in the formation of unacceptable defects on the glass surface. Although, the hydrophilic surfaces caused an increased risk of fogging on the inner vial surface [21].…”
Section: Introductionmentioning
confidence: 99%